2015
DOI: 10.1520/gtj20140216
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Optical Clarity of Transparent Soil Using the Modulation Transfer Function

Abstract: Transparent synthetic soils have been developed as a soil surrogate to enable internal visualization of geotechnical processes in physical models. Transparency of the soil dictates the overarching success of the technique; however, despite this fundamental requirement, no quantitative framework has yet been established to appraise the visual quality of transparent soil. Previous approaches to assess and optimize transparency quality included an eye chart assessment method, although this approach is highly subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…It is also interesting to note that the trend line turning point corresponds to the temperature at which the material was calibrated to yield optimum transparency (i.e., 20 C). This is in good agreement with previous research reported by Stanier (2011) and Black and Take (2015), and provides further confidence in the pixel intensity-temperature relationship established and presented in Fig. 6.…”
Section: Figsupporting
confidence: 93%
See 4 more Smart Citations
“…It is also interesting to note that the trend line turning point corresponds to the temperature at which the material was calibrated to yield optimum transparency (i.e., 20 C). This is in good agreement with previous research reported by Stanier (2011) and Black and Take (2015), and provides further confidence in the pixel intensity-temperature relationship established and presented in Fig. 6.…”
Section: Figsupporting
confidence: 93%
“…Works using this approach include examination of failure mechanics of helical screw piles (Stanier et al 2013), stone column groups (Kelly 2013), and tunnel induced settlements (Ahmed and Iskander 2010) soil plugging behavior during press-in piling of tubular piles (Black 2012;Forlati and Black 2014). The success of transparent soil modeling has long been considered reliant on producing a soil surrogate that offers the highest optical clarity, with low transparency being considered detrimental to the modeling technique (Black and Take 2015). However, recent work by Siemens et al (2010) and Peters et al (2011) embraced the loss of soil transparency as a positive characteristic for the purpose of modeling unsaturated soil phenomena.…”
Section: Transparent Soil Modelingmentioning
confidence: 99%
See 3 more Smart Citations